A Phenomenology of Return: Forgiveness and Atonement in Emmanuel Levinas and Abraham Joshua Heschel - Palmisano, SJ, Joseph Redfield (Studies in Christian-Jewish Relations, 2012)
A way of remembering the sanctity of the other may inform and guide Christianity towards a more robust dialogical perspective with others. This essay will widen the question for the Christian community by exploring how Judaism remembers those who have been wronged. The methodology is phenomenological in so far as the essay explores the phenomenon of return (teshuva) through the thought of Emmanuel Levinas in dialogue with Abraham Joshua Heschel. When Christianity regards Judaism as a living tradition, instead of a relic, atonement and forgiveness rises to the broader horizon of being ethically relevant in an interreligious context. The real-time teaching (talmud) from righteousness (tzedakah) in Judaism opens opportunities for dialogue with otherness. This exploration of what forgiveness and atonement may mean in a post-Shoah world for Jews and Christians may only contribute to how dialoguing with otherness is a necessary form of return (teshuva) for all interreligious dialogues.